2016
DOI: 10.4322/0104-4931.ctoar0525
|View full text |Cite
|
Sign up to set email alerts
|

O Uso Dos Conceitos De Ocupação E Atividade Na Terapia Ocupacional: Uma Revisão Sistemática Da Literatura

Abstract: Resumo: Introdução: Os conceitos de ocupação e atividade são conceitos centrais para a Terapia Ocupacional, e vêm sendo utilizados diversamente ao longo do tempo, conforme o país, a cultura e o período histórico. Objetivo: O presente estudo tem como objetivo contribuir para o conhecimento do uso dos conceitos de atividade e ocupação na Terapia Ocupacional, na literatura internacional e nacional. Método: Foi realizada uma revisão sistemática de literatura sobre o tema. Resultados: A pesquisa na literatura explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 10 publications
1
10
0
16
Order By: Relevance
“…The data from this research corroborated with the work of Salles & Matsukura (2016) and Lima et al (2013), who found that "activity" is the most evident term in Brazilian literature. In the research by Lima et al (2013), the term activity was found in 73% of the analyzed sample.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The data from this research corroborated with the work of Salles & Matsukura (2016) and Lima et al (2013), who found that "activity" is the most evident term in Brazilian literature. In the research by Lima et al (2013), the term activity was found in 73% of the analyzed sample.…”
Section: Discussionsupporting
confidence: 89%
“…Several authors (Medeiros, 2003;Poellnitz, 2018;Lima et al, 2013;Quarentei et al, 2008;Falcão & Guimarães, 2004;Joaquim et al, 2003;Toyoda & Akashi, 1993;Galheigo, 1988) debated about the terms occupation and activity and how they are used as synonyms, or they conceptualize or show other meanings, such as action, doing, praxis, among other terminological variations of the Brazilian occupational therapy. Silva (2013) and Salles & Matsukura (2016) point out that in the publications in this area, polysemy and plurality are evident in the construction of a field marked by diverse practices and knowledge. Benetton (2008) states that there is an indiscriminate use in the terms of activity, occupation, and occupational activity in Brazil, in which the "carelessness" in the adoption of the term occupation and its correlates make a conceptual confusion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was contextualized within Brazilian occupational therapy, specifically social occupational therapy (Malfitano et al, 2014). Due to the meanings that the word occupation has in Brazil, which are historically linked to alienation processes and moral treatment in psychiatry, the concept of occupation is not widely used in Brazilian research and scholarship (Magalhães & Galheigo, 2010;Salles & Matsukura, 2016). Instead, concepts such as cotidiano have been adopted.…”
mentioning
confidence: 99%